(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This scientific article examines the expeditions, works and contributions of A.A. Asankanov as an outstanding scientist who made a great contribution to the field of history and culture of the Kyrgyz people, using written, oral and archaeological materials to study the history, ethnogenesis, nomadic culture and statehood of the Kyrgyz Republic. Kyrgyz people, who brought new facts to science.